Physiological and biochemical responses of Limonium tetragonum to NaCl concentrations in hydroponic solution - Jang, Seong-Nam; Kang, Min-Ji; Kim, Yun Na; Jeong, Eun Ju; Cho, Kye Man; Yun, Jae Gil; Son, Ki-Ho (Frontiers in Plant Science, 2023)
Limonium (L.) tetragonum (Thunb.) A. A. Bullock, a halophyte that grows all over the southwest coast of Korea, is a medicinal plant with various pharmacological effects. The salt defense mechanism stimulates the biosynthesis of various secondary metabolites and improves functional substances. In this study, we investigated the optimal NaCl concentration for the growth and enhancement of secondary metabolites in hydroponically grown L. tetragonum by using the characteristics of halophytes that 0-mM NaCl the production of various secondary metabolites through the salinity defense mechanism. The seedlings grown for 3 weeks in a hydroponic cultivation system were treated with 0-, 25-, 50-, 75-, and 100-mM NaCl in Hoagland’s nutrient solution for 8 weeks. No significant effect on the growth and chlorophyll fluorescence was observed for the NaCl concentrations below 100-mM. The increase in the NaCl concentration resulted in the decrease in the water potential of the L. tetragonum leaves. The Na+ content accumulated in the aerial part increased rapidly and the content of K+, which acts as an antagonist, decreased with the increase in NaCl concentrations in hydroponics. The total amino acid content of L. tetragonum decreased compared to the 0-mM NaCl, and most of the amino acid content decreased as the NaCl concentration increased. In contrast, the content of urea, proline (Pro), β-alanine, ornithine, and arginine was increased with an increase in NaCl concentration. The Pro content at 100-mM NaCl accounted for 60% of the total amino acids and was found to be a major osmoregulator as an important component of the salt defense mechanisms. The top five compounds identified in the L. tetragonum were classified as flavonoids while the flavanone compound was detected only in the NaCl treatments. A total of four myricetin glycosides were increased in comparison to the 0-mM NaCl. Among the differentially expressed genes, a significantly large change in Gene ontology was seen in the circadian rhythm. NaCl treatment enhanced the flavonoid-based substances of L. tetragonum. The optimum NaCl concentration for the enhancement of secondary metabolites of the L. tetragonum in the vertical farm-hydroponic cultivation system was 75-mM NaCl.